Electronic structures of cyclometalated palladium complexes in the higher oxidation states1. Issue 37 (7th October 2015) - Nguyen, Bao N.; Adrio, Luis A.; Albrecht, Tim; White, Andrew J. P.; Newton, Mark A.; Nachtegaal, Maarten; Figueroa, Santiago J. A.; Hii, King Kuok (Mimi)
<x xml:space="preserve">Abstract</x> Electronic structures of Pd(ii), Pd(iii) and Pd(iv) complexes were examined using X-ray crystallography and absorption spectroscopy, supplemented by theoretical calculations.